2018
DOI: 10.20944/preprints201802.0095.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

EP4 as a Therapeutic Target for Aggressive Human Breast Cancer

Abstract: G protein-coupled receptors (GPCRs, also called seven-transmembrane or heptahelical receptors) are a superfamily of cell surface receptor proteins that bind to many extracellular ligands and transmit signals to an intracellular guanine nucleotide-binding protein (G protein). When a ligand binds, the receptor activates the attached G-protein by causing the exchange of Guanosine-5'-triphosphate (GTP) for guanosine diphosphate (GDP). They play a major role in many physiological functions as well as in the patholo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 69 publications
1
13
0
Order By: Relevance
“…Evidence points a close proportional relation regarding the activity of COX‐2 and aromatase activity, E 2 production,and pregnancy rate (Blom, Tan, Hughes, Tekpetey, & Rafea, 2018; Stevenson & Pulley, 2016). Consistent with our results, serum E 2 concentration among NSAID users was significantly lower than nonusers of NSAIDs (Hudson et al, 2008; Majumder, Nandi, Omar, Ugwuagbo, & Lala, 2018). When the combination of ASA with AA added to CGCs, the synthesis of both E 2 was induced.…”
Section: Discussionsupporting
confidence: 91%
“…Evidence points a close proportional relation regarding the activity of COX‐2 and aromatase activity, E 2 production,and pregnancy rate (Blom, Tan, Hughes, Tekpetey, & Rafea, 2018; Stevenson & Pulley, 2016). Consistent with our results, serum E 2 concentration among NSAID users was significantly lower than nonusers of NSAIDs (Hudson et al, 2008; Majumder, Nandi, Omar, Ugwuagbo, & Lala, 2018). When the combination of ASA with AA added to CGCs, the synthesis of both E 2 was induced.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, it was shown that COX2/ mPGES1(Ptges)/PGE 2 pathway upregulates PD-L1 expression in tumor-associated macrophages (TAM) and MDSC, which contributes to the immunosuppression in bladder cancer [22]. In addition, upregulated PGE 2 receptor EP4 was found in COX2-expressing triple-negative breast cancer, whereas targeting EP4 was suggested to benefit the therapeutic effect of PD-L1 inhibitors [44].…”
Section: Discussionmentioning
confidence: 99%
“…However, anti-cancer drugs that specifically target GPCRs are not currently available [9]. The prostanoid receptors represent the most notable family of validated pharmacological targets in a variety of diseases, including cancer [10].…”
mentioning
confidence: 99%